Pengembangan Media Pembelajaran Gamifikasi Materi Tata Surya Kelas VI Sekolah Dasar - Wasetya Fatharani; Diana Ariani; Erry Utomo (Universitas Negeri Jakarta, 2022)
Gamification is one of the interventions for delivery of material that is abstract into concrete, one of which is in the material of the Solar System. As for the characteristics of 6th grade elementary school students, their cognitive level is at the concrete operational stage, so the delivery of Solar System material needs to be packaged in a concrete and fun way. This development research aims to produce a product in the form of Gamification Learning Media for 6th grade elementary school materials. This gamification learning media product refers to the Rapid Prototyping model which has 5 stages, namely Assess Needs and Analyze Content, Set Objectives, Construct Prototype, Utilization Prototype, and Installing the Final System. The gamification learning media product has gone through an expert review using a Likert scale with the results of material experts of 3.75 (very good), media experts of 4.00 (very good) and learning design experts of 3.70 (very good). As well as user trials using the Guttman scale obtained from 15 indicators there are 2 indicators that get a disagreeable response, so that gamification learning media is attractive to users. Abstrak Gamifikasi menjadi salah satu intervensi dalam penyampaian materi yang bersifat abstrak menjadi konkret, salah satunya pada materi Tata Surya. Karakteristik siswa kelas VI sekolah dasar tingkat kognitifnya pada tahap operasional konkret, sehingga penyampaian materi Tata Surya perlu dikemas menjadi konkret dan menyenangkan. Penelitian pengembangan ini bertujuan untuk menghasilkan produk berupa Media Pembelajaran Gamifikasi materi Tata Surya kelas VI sekolah dasar. Produk media pembelajaran gamifikasi ini mengacu pada model Rapid Prototyping yang memiliki 5 tahap, yaitu Asses Needs and Analyze Content, Set Objectives, Construct Prototype, Utilization Prototype, dan Installing the Final System. Produk media pembelajaran gamifikasi telah melalui expert review menggunakan skala Likert dengan hasil ahli materi sebesar 3,75 (sangat baik), ahli media 4,00 (sangat baik) dan ahli desain pembelajaran 3,70 (sangat baik). Serta uji coba pengguna menggunakan skala Guttman diperoleh dari 15 indikator terdapat 2 indikator yang mendapatkan respon tidak setuju, sehingga media pembelajaran gamifikasi menarik bagi pengguna.